GOCE CLOSED-LOOP SIMULATION - Oberndorfer H.; Muller J. (My University, 2002)
GOCE (gravity field and steady-state ocean circulation explorer) will provide a global model of the Earth's gravity field with high spatial resolution and high accuracy. The gravity measurements are derived from a combination of different sensor readouts. On one hand, the satellite itself is the test mass which is tracked by GPS, on the other hand, accelerometers are combined to a gradiometer to measure gravity gradients. To extract the gravitational signal, it is necessary to observe the non-gravitational forces disturbing the satellite dynamics, and to control these effects by thrusters or correct them in post-processing. Therefore GPS, star trackers and the gradiometer are employed for orbit control, attitude control, precise positioning and gravity field measurements. This paper focuses on the investigation of the accuracy of gradiometer measurements which depend on the complete system performance. The gradiometer measurements were simulated as time series using the software SIMULINK. Differences between input gravity gradients and simulated gradiometer measurements served as input for the derivation of error power spectral densities (PSD's). The latter are used for further error analyses of the scientific end-products (e.g. spherical harmonic coefficients, geoid heights, gravity anomalies). The errors to be considered are caused by the imperfection of any sensor or actuator and their measurement noise. Moreover, the geometry (position and orientation) of the several instruments with respect to each other have been taken into account with a certain accuracy. All these errors and their couplings affect the measurements and consequently the end-products. In terms of power spectral densities, the mission requirement of the gradiometer is 4 mE/Hz white noise with a 1/f-behaviour below 1 mHz. Analyses and simulations allowed the determination of the full error budget in the spectral domain, based on all types of realistic error sources. The main error sources have been identified and it could be shown that the mission requirements are fulfilled.